THE MERGER OF TOP UNIVERSITY – EXPLORING THE OPERATIONAL EFFICIENCY OF NYCU IN TAIWAN FROM A FINANCIAL PERSPECTIVE - Chiou Rung Chen (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This study utilized DEA to empirically evaluate the operational efficiency of Taiwan's TOPU NYCU from a self-financing perspective between 2012 and 2023. The results demonstrated that although the merged NYCU maintained increasing returns to scale (IRS) in research, his teaching turned to more severe decreasing returns to scale (DRS) beginning from the second year post-merger. This shift, coupled with a simultaneous surge in four input factors—particularly administrative and general expenses—drove NYCU's overall operations into increasingly severe scale inefficiency. The findings confirmed that the merger-induced diversity of fields, disciplines, and missions, along with the multi-campus structure, resulted in disEOSCA and disEOSCOeconomies of scale and scope. Additionally, the study identified NYCU's strong resilience against declining birthrate impacts, while noting that Taiwan's current public university tuition system undermined institutional financial stability and efficiency.